2014
DOI: 10.1248/bpb.b14-00044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin Analogues for Inhibiting Human Prostate Cancer Cells and the Growth of Human PC-3 Prostate Xenografts in Immunodeficient Mice

Abstract: Four curcumin analogues ((2E,6E)-2,6-bis(thiophen-3-methylene) cyclohexanone (AS), (2E,5E)-2,5-bis(thiophen-3-methylene) cyclopentanone (BS), (3E,5E)-3,5-bis(thiophen-3-methylene)-tetrahydropyran-4-one (ES) and (3E,5E)-3,5-bis(thiophen-3-methylene)-tetrahydrothiopyran-4-one (FS) as shown in Fig. 1) with different linker groups were investigated for their effects in human prostate cancer CWR-22Rv1 and PC-3 cells. Compounds FS and ES had stronger inhibitory effects than curcumin, AS and BS on the growth of cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
2
9
0
2
Order By: Relevance
“…The present study identified that analogues with tetrahydrothiopyran-4-one (FN) as the linker were more potent inhibitors than those with tetrahydropyran-4-one (EN), cyclohexanone (AN) or cyclopentanone (BN). Earlier studies revealed that the six-membered cyclohexanone ring system is, in general, superior to the five-membered cyclopentanone system for inhibiting the growth of several cancer cell lines (23,24). The current results confirmed this structure activity association, as pyridine cyclohexanone curcumin analogues displayed stronger inhibitory activities than pyridine cyclopentanone curcumin analogues.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study identified that analogues with tetrahydrothiopyran-4-one (FN) as the linker were more potent inhibitors than those with tetrahydropyran-4-one (EN), cyclohexanone (AN) or cyclopentanone (BN). Earlier studies revealed that the six-membered cyclohexanone ring system is, in general, superior to the five-membered cyclopentanone system for inhibiting the growth of several cancer cell lines (23,24). The current results confirmed this structure activity association, as pyridine cyclohexanone curcumin analogues displayed stronger inhibitory activities than pyridine cyclopentanone curcumin analogues.…”
Section: Discussionsupporting
confidence: 82%
“…Our previous study and another previous study indicated that cyclohexanone-containing analogues of curcumin have more potent anticancer activities than curcumin (23,24). Further modification of cyclohexanone-containing curcumin analogues by replacing the ortho-hydroxylmethoxyl benzene with a pyridine ring strongly enhanced the anticancer activities of these curcumin analogues (23).…”
Section: Discussionmentioning
confidence: 84%
“…To circumvent these problems, numerous analogs of curcumin have been synthesized. For example, the potential activity of recently synthesized curcumin analogs (2E,6E)-2,6-bis(thiophen-3-methylene) cyclohexanone (AS), (3E,5E)-3,5-bis(thiophen-3-methylene)-tetrahydrothiopyran-4-one (FS), A501, and GO-Y031 has been studied in prostate cancers, NSCLC cells and gastric cancers [1416]. …”
Section: Introductionmentioning
confidence: 99%
“…; resveratrol, a polyphenolic stilbene found in grapes; silibinin, a naturally-occurring flavonoid produced by milk thistle and melatonin, an indole that is mainly produced by the pineal gland in vertebrates but also found in edible plants [18], was investigated. All of them have shown effects against tumor growth in cells or in rodent models of prostate cancer [19], [20], [21], though, the molecular pathways involved in their mechanisms of action, in particular the redox signaling pathways altered, still remain unclear. In this study, we aim to investigate ROS-mediated apoptosis signaling pathways induced by these bioactive compounds that have displayed antioxidant or pro-oxidant activities in vitro [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%